Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Angkatan 2024 Memilih Program Studi S1 Pendidikan Teknik Mesin FT UNP - Jumadil Ashari; Andre Kurniawan; Junil Adri; Wanda Afnison (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This research investigates the underlying factors that shape the interest of students from the 2024 cohort in enrolling in the Bachelor of Mechanical Engineering Education Program at the Faculty of Engineering, Universitas Negeri Padang. Utilizing a descriptive quantitative methodology, data were gathered through a structured, closed-ended questionnaire administered to the entire cohort, which consisted of 89 students. The analysis reveals that the overall level of student interest is categorized as high, with a notable percentage of 55%. Several key variables were identified as influential: (1) self-awareness factors encompassing physical capabilities, intellectual aptitude, intrinsic motivation, and innate talent were rated in the very high category at 56%; (2) familial influences such as the provision of information, emotional support, and parenting styles also ranked very high at 46%; (3) school-related elements including the accessibility of school information systems, teacher roles, peer dynamics, and hands on learning experiences were classified in the high category with 44%; and (4) social media engagement specifically the frequency of use and the quality of educational content was likewise in the high category, scoring 48%. These findings underscore the multifaceted nature of student decision-making, with self-awareness emerging as the most prominent determinant in shaping academic program choices. The study highlights the need for educational institutions to consider these interrelated dimensions when developing recruitment strategies and academic guidance frameworks.